Changes in Protonation Sites of 3-Styryl Derivatives of 7-(dialkylamino)-aza-coumarin Dyes Induced by Cucurbit[7]uril - Alcázar, Jackson J.; Márquez, Edgar; García-Río, Luis; Robles-Muñoz, Agustín; Fierro, Angélica; Santos, José G.; Aliaga, Margarita E. (Frontiers in Chemistry, 2022)
The incorporation of a guest, with different basic sites, into an organized system (host), such as macrocycles, could stabilize, detect, or promote the formation of a certain protomer. In this context, this work aimed to study the influence of cucurbit[7]uril (CB7) on dyes such as 7-(dimethylamino)-aza-coumarins, which have more than one basic site along their molecular structure. For this, three 3-styryl derivatives of 7-(dialkylamino)-aza-coumarin dyes (SAC1-3) were synthesized and characterized by NMR, ESI-HRMS and IR. The spectral behaviour of the SACs in the absence and presence of CB7 was studied. The results showed large shifts in the UV-vis spectrum in acid medium: a hypsochromic shift of 5400 cm-1 (SAC1-2) and 3500 cm-1 (SAC3) in the absence of CB7 and a bathochromic shift of 4500 cm-1 (SAC1-3) in the presence of CB7. The new absorptions at long and short wavelengths were assigned to the corresponding protomers by computational calculations at the density functional theory (DFT) level. Additionally, the binding mode was corroborated by molecular dynamics simulations. Findings revealed that in the presence of CB7 the heterocyclic nitrogen was preferably protonated instead of the dialkylamino group. Namely, CB7 induces a change in the protonation preference at the basic sites of the SACs, as consequence of the molecular recognition by the macrocycle.